COVID-19 Care in India: Evolving Paradigms from Public Health to Critical Care - Joshi, Shashank R (Journal of the Association of Physicians of India, 2020)
Covid-19 pandemic in India has rapidly grown though we have a low case fatality rate, high recovery rate and large population is asymptomatic or presymptomatic. Public health measures to close the tap across the country need hypervigilance and follow simple dictum of aggressive testing, tracing and isolation. The covid cases need an early diagnosis with treat and care model. Most can be managed with home isolation under telemedicine supervision with oxygen saturation screening by a simple six minute walk test. Hospitalised cases have emerging evidence in different therapies from antivirals, steroids, immunologic to heparins but high flow oxygen, prone position and supportive care remains the cornerstone in critical care with nursing and nutrition. Vaccine research is ongoing but currently only social vaccine can mitigate the pandemic. Covid appropriate behaviour of Masking, sanitisation and physical distancing with immune modulating behaviour like adequate sleep, digital detox for two hour and clean well ventilated environment is the key with breathing exercises including yoga and positive mental health and avoidance of crowds the only vaccine to live with covid -19 today.